1983
DOI: 10.1128/aem.46.3.694-697.1983
|View full text |Cite
|
Sign up to set email alerts
|

N 2 Fixation by Azospirillum brasilense and Its Incorporation into Host Setaria italica

Abstract: Growth and nitrogen fixation were followed during the life cycle of Setaria italica (foxtail millet) inoculated with Azospirillum brasilense in controlledenvironment growth chambers. The plants were fertilized at seeding with a limiting amount of combined nitrogen and maintained with an N-free mineral solution. During maturation of the plants, substantial nitrogenase activity, measured by acetylene reduction, developed in the rhizosphere, with total fixation estimated to be equivalent to 20% of the N in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(30 citation statements)
references
References 7 publications
0
28
0
2
Order By: Relevance
“…Gyaneshwar et al (2002) detailed the acetylene reduction activity of surface-colonizing bacteria; most of the bacteria in their study, particularly the bacteria expressing the nitrogenase Fe-protein, were observed only on the root surfaces. The transfer of nitrogen from the root surface to plants in cases where large bacterial populations are present on the root surface or in the rhizosphere presumably occurs through bacterial decomposition (Okon et al 1983). In rice inoculated with Herbaspirillum seropedicae, the significant increase in plant growth observed by Gyaneshwar et al (2002) and James et al (2002) in parallel with a significant increase in the quantity of fixed N suggests that endophytic bacteria contribute to plant growth by providing fixed N. However, endophytic bacteria are also reported to promote plant growth without enhancing N content, implying that they influence plant growth by other means (Gyaneshwar et al 2001), for example, by the excretion of phytohormones (Chi et al 2005).…”
Section: Nitrogenase Activity In Broccoli Plantsmentioning
confidence: 99%
“…Gyaneshwar et al (2002) detailed the acetylene reduction activity of surface-colonizing bacteria; most of the bacteria in their study, particularly the bacteria expressing the nitrogenase Fe-protein, were observed only on the root surfaces. The transfer of nitrogen from the root surface to plants in cases where large bacterial populations are present on the root surface or in the rhizosphere presumably occurs through bacterial decomposition (Okon et al 1983). In rice inoculated with Herbaspirillum seropedicae, the significant increase in plant growth observed by Gyaneshwar et al (2002) and James et al (2002) in parallel with a significant increase in the quantity of fixed N suggests that endophytic bacteria contribute to plant growth by providing fixed N. However, endophytic bacteria are also reported to promote plant growth without enhancing N content, implying that they influence plant growth by other means (Gyaneshwar et al 2001), for example, by the excretion of phytohormones (Chi et al 2005).…”
Section: Nitrogenase Activity In Broccoli Plantsmentioning
confidence: 99%
“…strain BH72 and kallar grass (Hurek et al ., ), Klebsiella spp. and wheat (Iniguez et al ., ) or H. seropedicae Z67 and rice (Boddey et al ., ; Gyaneshwar et al ., ) and Azospirillum brasilense in Setaria italica (Okon et al ., ). However, the levels of nitrogen fixation reported would provide little or no contribution to the plant's overall nitrogen demand.…”
Section: Introductionmentioning
confidence: 97%
“…which are transferred to their host plants appear to be small (3,21,29). Investigations in which the 15N isotope dilution technique was used indicated that most of the fixed nitrogen remained below ground, probably still bound to bacterial cells, and contributed only very little to the upper plant parts (7,34,38). In experiments performed with wheat plants that were monoxenically associated with Azospirillum brasilense, only 1 to 2% of the shoot nitrogen originated from atmospheric sources (6a).…”
mentioning
confidence: 99%